2019
DOI: 10.1002/pen.25275
|View full text |Cite
|
Sign up to set email alerts
|

A simple model for the semicontinuous heterophase polymerization: Ethyl methacrylate as a case example

Abstract: A simple but comprehensive model considering homogeneous and micellar nucleation, coagulation, entry of radicals to particles and to micelles and radicals' exit from particles, is presented. The model is validated, in a starved semicontinuous heterophase polymerization of ethyl methacrylate, at three monomer addition rates. The model accurately describes the overall and instantaneous conversion, the average particle density and diameter, and the number and weight average molar masses evolutions over time. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
1
1
Order By: Relevance
“…1, it can be seen that a controlled starved process was not achieved, due to the fact that the conversion against time curve does not have a constant slope. This nding is in contrast to the work reported by Pérez-García et al [28] or in Alvarado et al [29].…”
Section: Variable/ Parametercontrasting
confidence: 99%
See 1 more Smart Citation
“…1, it can be seen that a controlled starved process was not achieved, due to the fact that the conversion against time curve does not have a constant slope. This nding is in contrast to the work reported by Pérez-García et al [28] or in Alvarado et al [29].…”
Section: Variable/ Parametercontrasting
confidence: 99%
“…In both gures it can be observed that, even with a semi-continuous process, two clear rate intervals are present, as opposed to the classic batch emulsion polymerization. As a matter of fact, in a semi-continuous starved process a constant rate of polymerization should be achieved [28,29]. Figure 4 shows that a master curve can be constructed when plotting rate of polymerization against conversion, where all the runs using clay lie almost on a single trajectory --making clear that the only outlier is the curve where no clay was used.…”
Section: Variable/ Parametermentioning
confidence: 99%